How effective is Brief Smoking Cessation Counseling in Infertile Couples? - Mahshid Aryanpur; Gholamreza Heydari; Majid Tarahomi; Mohamad Mehdi Akhondi; Hooman Sadri Ardakani; Mohamad Reza Masjedi (Tehran University of Medical Sciences, 2010)
Objective: Infertility is an important social concern. Environmental factors such as smoking and tobacco consumption can affect sperm and follicular function and infertility. Smoke cessation reduces its complications and makes infertility treatment more effective which motivates and encourages infertile smokers to consider quitting. The aim of current study was to assess brief smoking cessation counseling efficacy in infertile couples referring to Avicenna center. Materials and Methods: This is a Descriptive cross-sectional study. Smokers referred to Avicenna infertility clinic with complain of primary infertility during 2008-2009 were studied. Data were collected through questionnaire. Patients received tobacco cessation brief advice and educational material package of ill effects of tobacco consumption on general health and infertility.  Success in quitting was assessed 6 months after the first visit. Results: Seventy cases were studied with mean age of 36.45±6.3 which 68(%97.1) were male. The mean of smoke consumption duration was 17.78±7.49 and the mean duration of infertility was 5.56±4.0 year. Forty one individuals (59.4%) had mild nicotine dependence.  Mean knowledge level about tobacco harms was 0.57±0.79 (from total of 4 points) and attitude mean was 18.50±2.95 (from total of 24 points).  Estimating quit success rates, 41 individuals (63%) quitted but it was unrelated to cessation factors. Conclusion: It seems that according to high motivation of this group, smoke cessation brief advice and increasing knowledge through educational package is effective. It is recommended that smoke cessation brief advice and knowledge increment to be added to infertility treatment program.